Per os infectivity factors are essential for bracovirus infection and wasp parasitism - Xi Wang; Zhe Lin; Fei Wang; Hengrui Hu; Heya Na; Tao Zhang; Just M. Vlak; Zhen Zou; Manli Wang; Zhihong Hu (Proceedings of the National Academy of Sciences, 2026)
Many parasitoid wasps in the family Braconidae rely on bracoviruses to parasitize lepidopteran hosts. Bracoviruses evolved from a virus in the family Nudiviridae , while nudiviruses are closely related to baculoviruses. A per os infectivity factor (PIF) complex is essential for oral infection of hosts by baculoviruses. Bracoviruses encode 8 PIF homologs but have no per os infection route because wasps inject virions into hosts. Thus, the mechanism underlying how bracoviruses enter lepidopteran host cells is unknown. Here we used the parasitoid Microplitis mediator , its lepidopteran hosts Mythimna separata and Helicoverpa armigera , and M. mediator bracovirus (MmBV) to elucidate the function of bracoviral PIFs. We identified a ~720-kDa PIF complex on the envelope of MmBV virions. In addition to PIF0-4, PIF6, and PIF8, we identified two other proteins in the MmBV PIF complex: PIF5-3 and a wasp encoded β-propeller domain-containing protein named P52. The other two PIF5 paralogs (PIF5-1 and PIF5-2) were not associated with the PIF complex. Knocking down any component in the PIF complex resulted in degradation, which suggested all components are essential for stability. Using expression of an MmBV ankyrin gene as a marker, we determined that MmBV PIFs are essential for systemic infection of host larvae. Knocking down any PIF complex component or double silencing of PIF5-1 and PIF5-2 also resulted in failed parasitism as measured by no survival of M. mediator offspring. Altogether, our results demonstrate an essential role for the MmBV PIFs in systemic infection of a lepidopteran host.